Principles of Money and Banking: related to national income and fiscal policy - Lindholm, Richard. W; Balles, John. J; Hunter, John. M (New York: Norton & Company, 1954)
This book is written from the point of view that the principal function of the first course in money and banking is to provide the means for making a sound appraisal of basic monetary issues. The book is divided into eight parts. Part One: The Wellsprings of Our Monetary System. Part Two: Money Theory. Part Three: The Framework of the Money and Banking System. Part Four: The Functioning of the Commercial Banking System. Part Five: Monetary Policy. Par Six: Fiscal Policy. Part Seven: Financial Institutions Other than Commercial and Central Banks. Part Eight: International Finance.
includes index
rpm 10/04/2018
Loans
Keywords: Money and Banking; Money; Banking